2006
DOI: 10.5424/sjar/2006044-212
|View full text |Cite
|
Sign up to set email alerts
|

Soil physical properties and root activity in a soybean second crop/maize rotation under direct sowing and conventional tillage

Abstract: Soil degradation is the result of interactions involving the soil itself, human activity, climate, relief, and vegetation. These can lead to changes in —or even the loss of— certain characteristics of the soil, reducing its present and future productive capacity. The aim of this study was to determine the behaviour of a number of soil physical variables and total organic carbon content, as well as the root activity and yield of crops grown in rotation (soybean in 1998/1999 and maize in 1999/2000) under direct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 15 publications
1
7
0
1
Order By: Relevance
“…The increase in seed yield with NT management may be due to improved soil structure and surface residue cover which enhance water infi ltration and root growth and/or reduce water losses through evaporation from the soil (Diaz-Zorita et al 2004, Tarkalson et al 2006). In contrast, Barrios et al (2006) observed significantly higher yields in soybean crops under conventional tillage than in no tillage system in a rotation maize/soybean. At the same time, Lança Rodrígues et al (2009) found no signifi cant differences in soybean seed yields among tillage systems.…”
Section: Seed Yieldmentioning
confidence: 58%
“…The increase in seed yield with NT management may be due to improved soil structure and surface residue cover which enhance water infi ltration and root growth and/or reduce water losses through evaporation from the soil (Diaz-Zorita et al 2004, Tarkalson et al 2006). In contrast, Barrios et al (2006) observed significantly higher yields in soybean crops under conventional tillage than in no tillage system in a rotation maize/soybean. At the same time, Lança Rodrígues et al (2009) found no signifi cant differences in soybean seed yields among tillage systems.…”
Section: Seed Yieldmentioning
confidence: 58%
“…Although different characteristics of soybean have been previously studied in this or in a similar framework (Santos et al, 1994a;Barrios et al, 2006;Di Ciocco et al, 2008), reported results differed considerably depending on the considered trait. This fact may reflect a lack of suitability in certain culture traits in order to describe the effects of management techniques and coverages.…”
Section: Introductionmentioning
confidence: 65%
“…In addition, Kluthcouski et al (2000) observed the same between different tillage systems. However, Barrios et al (2006) observed significantly higher yields in soybean crops under CT than in NT systems in a rotation maize/soybean. Lopes et al (2007) found significantly higher yields in soybean crops under CT compared to NT depending on the previous cover used, which were different from the ones used in the current study.…”
Section: Cover Cropsmentioning
confidence: 92%
See 1 more Smart Citation
“…Os maiores valores de Mi observados nas profundidades de 0,0 -0,10 m e 0,30 -0,40 m (Tabela 2) possivelmente, é consequência da menor resistência à penetração do solo, pois nessas profundidades os valores de porosidade total também são maiores. As camadas intermediárias podem apresentar aumento na densidade do solo, visto que o acúmulo dos resíduos vegetais em SPD e a umidade do solo nas camadas superficiais é maior, propiciando condições que favoreçam o crescimento radicular, e consequentemente maior Mi e PT (BARRIOS et al, 2006). Os maiores valores de DS foram observados nas profundidades 0,0 -0,10 m; 0,10 -0,20 m e 0,20 -0,30 m (Tabela 2).…”
Section: Atributos Físicos Do Solounclassified